MENGUJI PENGARUH PARAMETER GEOKIMIA BATUBARA FORMULA PARKASH 1983 DALAM MEMPENGARUHI PENINGKATAN KONVERSI HASIL PENCAIRAN - Harli Talla (JURNAL KONVERSI, 2018)
This research aims to test the parameters of coal geochemical such as virinite+liptinite, volatile matter and sulfur content used by Parkash (1983) to calculate the liquid potential of a coal sample and compare with laboratory scale conversion. Coal liquefaction in laboratory was carried out on the autoclave 5 liter, temperature is 425ºC and holding time is 60 minutes. the calculation of the conversion with Parkash formula (1983) reached 63.25% and laboratory conversion of 66,45 % (conversion without catalyst), the difference is 3,2 %. These results indicate that liquid conversion is influenced by vitrinite + liptinite macerals, volatile matter and sulfur content on the low rank coal liquefaction.